Sistem Informasi Geografis Lokasi Klinik Gigi di Kota Medan dengan Menggunakan Algoritma Tabu Search (TS) - Putri Nuri Hasbi Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2020)
As for the search for the location of dental clinics at this time is the existence of dental clinic locations in the city of Medan a little. Because of the small number, it is difficult for the community to find the location of the dental clinic. And requires a system to search the intended location. Where in this system there is location information, which consists of the name and address to get to the location of the dental clinic using the Android-based taboo search algorithm. Based on these problems, the writer will discuss about making Geographic Information Systems Searching Location of Dental Clinics in Medan City Using Taboo Search Algorithm. This system is made using Android-based, where in this system there is location information, consisting of an address, as well as route routes that can be used to get to the location of the Dental Clinic. In this system can only see and search for information on Dental Clinics in the city of Medan. With a simple and easy-to-understand system for the public to access information on locating Dental Clinic locations, it can be used as an effort to introduce technology based on geographic information systems to the public